Treating Steroid Refractory Intestinal Acute Graft-vs.-Host Disease With Fecal Microbiota Transplantation: A Pilot Study - Qi, Xiaofei; Li, Xuewei; Zhao, Ye; Wu, Xiaojin; Chen, Feng; Ma, Xiao; Zhang, Faming; Wu, Depei (Frontiers in Immunology, 2018)
Patients with steroid refractory gastrointestinal (GI) tract graft-versus-host disease (GvHD) have a poor prognosis and limited therapeutic options. To accurately assess the efficacy and safety of fecal microbiota transplantation (FMT) in treating steroid refractory GI tract GvHD, we conducted a pilot study involving eight patients. Having received FMTs, all patients' clinical symptoms improved, bacteria enriched, and microbiota composition reconstructed. They achieved a similar overall survival, and a progression-free survival better than patients who did not receive FMT. To treat steroid refractory GI tract aGvHD, FMT is efficient and safe.